ISCHEMIC STROKE PRESENTING AS ISOLATED DIZZINESS IN A PATIENT WITH TYPE 2 DIABETES MELLITUS AND CONGESTIVE HEART FAILURE: A CASE REPORT - Elsa Lase; Rio Tasti Surpa Rahmat Bintan; Kamila Auliya (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Ischemic stroke may manifest with a wide range of clinical symptoms, including atypical presentations such as dizziness, especially in patients with complex cardiovascular and metabolic risk profiles. This case report describes the clinical course and management of ischemic stroke in a patient with pre-existing cardiovascular disease and type 2 diabetes mellitus. Case: A 61-year-old woman with a history of cardiovascular disease and type 2 diabetes mellitus presented with sudden disorientation and persistent dizziness. On the second day of hospitalization, she developed right-sided weakness, facial asymmetry, and slurred speech. A head CT scan revealed infarctions in the left occipital lobe and left corona radiata. Due to the unavailability of thrombolytic therapy at the local hospital, the patient was managed conservatively with 80 mg aspirin, 75 mg clopidogrel, citicoline, and insulin. Discussion: Dizziness/vertigo is recognized but is often an overlooked symptom of ischemic stroke, particularly in posterior circulation strokes. Approximately 20% of ischemic strokes involve the vertebrobasilar system, where vertigo is a predominant symptom. Type 2 diabetes mellitus and cardiovascular comorbidities significantly increase the risk of ischemic events. Patients presenting with dizziness or vertigo are at higher risk of subsequent stroke or cardiovascular events compared to those without these symptoms. Conclusion: This case underscores the importance of recognizing dizziness as a potentially subtle and early manifestation of ischemic stroke, especially in patients with complex cardiovascular and metabolic risk profiles, such as type 2 diabetes mellitus. Prompt evaluation and appropriate management are crucial for preventing progression and improving outcomes.